Family background and income during the rise of the welfare state: brother correlations in income for Swedish men born 1932 - 1968 - Anders Björklund; Markus Jäntti; Matthew J. Lindquist (Institute for the Study of Labor (IZA), 2007)
The goal of this study is to examine trends in the importance of family background in determining adult income in Sweden. We investigate whether the association between family background and income in Sweden has changed for cohorts born 1932-1968. Our main finding is that the share of the variance in long-run income that is attributable to family background, the so-called brother correlation in income, has fallen by some 11 percentage points from 0.34 for the cohorts of brothers born in the early 1930s to below 0.23 for the cohorts born around 1950. From then on, the correlations have been more or less stable and are in line with earlier estimates. When we adjust income for the income return to years of schooling, we find constant brother correlations in income. The main effect is coming from changes in the distribution of schooling across cohorts. This finding is consistent with the hypothesis that education policies have been a key factor in equalizing life chances in Sweden.
Keywords: 330; Sozialer Status; Einkommen; Familiensoziologie; Korrelation; Schweden